Recurrent Pregnancy Loss with Hypertensive Complication, Obesity and Suspected APS: A Case Based Approach to Antenatal Care Challenges - Husna Bulkis Dasopang; Mulyanusa Amarullah Ritonga; Amillia Siddiq (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Recurrent miscarriage, defined as the loss of two or more consecutive pregnancies, is a multifactorial condition associated with genetic, hormonal, anatomical, autoimmune, and maternal age-related factors. In Indonesia, data remain limited; however, at Dr. Kariadi Semarang Hospital, 18.7% of recurrent miscarriage cases between 2015 and 2017 were reported as idiopathic. We report a case of a 23-year-old woman, G7P0A6, at 33-34 weeks' gestation, presenting with elevated blood pressure and a history of chronic hypertension since 2016 with poor medication adherence. Ultrasonography revealed symmetrical fetal growth restriction (FGR) with an estimated fetal weight of 1500-1800 grams, and an obstetric history notable for six first-trimester miscarriages, suggestive of antiphospholipid syndrome (APS). Physical examination showed a blood pressure of 160/110 mmHg and obesity (BMI 32.9 kg/m²) without other features of severe preeclampsia; fetal monitoring and Doppler studies were normal. The patient was diagnosed with chronic hypertension exacerbated by preeclampsia, symmetrical fetal, suspected APS, recurrent miscarriage, and obesity. Management included conservative hospitalization, administration of magnesium sulfate, corticosteroids, and antihypertensive therapy, with cesarean delivery planned after 34 weeks once fetal lung maturation was achieved. This case highlights the challenges of managing high-risk pregnancies complicated by APS, FGR, and hypertensive disorders, emphasizing the importance of adequate antenatal care, multidisciplinary coordination, and appropriate timing of delivery to optimize maternal and fetal outcomes.Keywords: Antenatal Care, Poor Obstetric, Recurrent Pregnancy Loss, Fetal Growth Restriction; Preganancy Termination.